Safeguarding human and planetary health demands a fertilizer sector transformation - Bindraban, Prem S.; Dimkpa, C.O.; White, J.C.; Franklin, F.A.; Melse-Boonstra, Alida; Koele, N.; Rodenburg, J.; Senthilkumar, Kalimuthu; Demokritou, P.; Schmidt, S. (Wiley, 2020)
Fertilizer nutrients are essential for food and nutrition security, but a large proportion of nutrients applied to soil are lost because they are unavailable to plants. The extent of these nutrient losses exceeds safe and sustainable limits. Societal awareness of this is limited because it can take many seasons for nutrient‐loss impacts to become visible. We propose that Innovative Fertilizers and Application Technologies (IFAT) could help reduce nutrient losses and thus reduce pressure on resources, and provide important micronutrients for human health. However, transformation of the fertilizer sector through stakeholder engagement, policy interventions, and public–private initiatives will be required to unlock the full potential of IFAT.SummaryStrategies for delivering sustainable food systems require significant reduction in yield gaps and food system inefficiencies. Mineral fertilizers will play a critical role in achieving both of these aims. However, reduction in nutrient losses from mineral fertilizer use to levels that are considered sustainable has not been achieved and has been estimated to be unachievable, even with optimized practices for current products. We argue that Innovative Fertilizers and Application Technologies (IFAT) are needed to address the daunting and interlinked food, agricultural, and environmental challenges facing humanity and the planet. We define IFAT as a set of fertilizer products and technologies that are designed by taking the physiological needs of plants (such as nutrient uptake, redistribution, and utilization) as the entry point in the fertilizer development process, rather than starting first with chemistry. This approach aims for the timely and targeted delivery of nutrients in balanced quantities. We propose that this can result in multiple food, agricultural, and environmental benefits, including increased yield, improvements in nutritional quality, enhanced crop resilience, and reduced emission of greenhouse gases (GHG), and leaching losses. However, the benefits of IFAT for human and environmental health have remained elusive. The major challenge for optimal use of IFAT is a transformation of the vast fertilizer sector by means of government policy interventions, societal responses, and significant investment in public and private research and development.